2003
DOI: 10.1002/aic.690490913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the size and amount of ZrO2 addition on properties of SrCo0.4Fe0.6O3−δ

Abstract: The effects of ZrO addition with ®arious particle sizes 1, 3, and 56 m and 2 ( ) ®arious amounts 0, 1, 3, 5, 7, 9 wt. % on structure, oxygen permeation, and stability ( ) of SrCo Fe O SCF were in®estigated. XRD and EDX analysis re®ealed that the 0 .4 0 .6 3 -␦ dissolution of Zr cation into the B site of SCF phase occurred with the addition of ZrO , resulting in a lattice expansion of SCF at ele®ated temperatures. The dissolution 2 amount of Zr in the SCF phase increased with a decrease of ZrO particle size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…When the membrane is calcined at 1523 K, the SrZrO 3 phase disappears and is dissolved into the perovskite-type phase. The dissolution of Zr 4+ induces the shift of the perovskite phase towards the lower angle [25]. From the above discussion, it can be indicated that the supported dense mixed-conducting membrane developed in our present work is suitable for the practical application such as the oxygen separation from air and membrane reactors for POM.…”
Section: Formation Of the Supported Dense Mixed-conducting Membranesmentioning
confidence: 39%
“…When the membrane is calcined at 1523 K, the SrZrO 3 phase disappears and is dissolved into the perovskite-type phase. The dissolution of Zr 4+ induces the shift of the perovskite phase towards the lower angle [25]. From the above discussion, it can be indicated that the supported dense mixed-conducting membrane developed in our present work is suitable for the practical application such as the oxygen separation from air and membrane reactors for POM.…”
Section: Formation Of the Supported Dense Mixed-conducting Membranesmentioning
confidence: 39%
“…Fig. 1b shows the XRD patterns of SCF and SrAl 2 O 4 -doped SCF powders, which are calcined at 950 • C for 5 h then annealed in helium at 700 • C for 5 h. After annealing, the characteristic peaks of SCF at 2q ≈ 32 • and 58 • split, which indicates a structure transition to the oxygen-vacancy-ordered brownmillerite phase of Sr 2 CoFeO 5 [18,22]. For SCFSA3, SCFSA5, SCFSA7, and SCFSA9, no obvious changes of phase structure are observed.…”
Section: Membrane Reactor Set-upmentioning
confidence: 44%
“…Several ways have been proposed to improve the structural stability of Sr(Co,Fe)O 3−ı oxides, such as substituting A and/or B site cations with more stable metal ions [14][15][16][17] and introducing certain amounts of second phase oxides into the perovskite-type oxides [18,19]. In our previous work, we found that introducing a little amount of fast-ion conductors, such as ZrO 2 , into SrCo 0.4 Fe 0.6 O 3−ı could not only stabilize the perovskite-type structure and reduce the variations of the oxygen nonstoichiometry of the perovskite phase, but also suppress the occurrence of the order-disorder phase transition in the oxygen permeation processes [18].…”
Section: Introductionmentioning
confidence: 47%
See 1 more Smart Citation
“…Oxygen permeation measurements were carried out in a vertical high‐temperature gas permeation system reported previously 12,18,19 . Membrane disks were sealed between two gold rings.…”
Section: Methodsmentioning
confidence: 99%